Non-Equilibrium Nano-Physics A Many-Body Approach - Fransson, Jonas; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The aim of this book is to present a formulation of the non-equilibrium physics in nanoscale systems in terms of many-body states and operators and, in addition, discuss a diagrammatic approach to Green functions expressed by many-body states. The intention is not to give an account of strongly correlated systems as such. The focus of this book ensues from the typical questions that arise when addressing nanoscale systems from a practical point of view, e.g. current-voltage asymmetries, negative differential conductance, spin-dependent tunneling. The focus is on nanoscale systems constituted of complexes of subsystems interacting with one another, under non-equilibrium conditions, in which the local properties of the subsystems are preferably being described in terms of its (many-body) eigenstates.
1 Many-body representation of physical systems -- 1.1 Many-body states -- 1.2 Two-level system -- 1.3 Many-body operators -- 1.4 Transition matrix elements -- References -- 2 Occupation number formalism -- 2.1 Perturbing the local levels -- 2.2 Occupations numbers -- 2.3 Single-level system -- 2.4 Two-level system in the Pauli spin blockade -- References -- 3 Many-body operator Green functions -- 3.1 Basic definitions -- 3.2 Equilibrium -- 3.3 Contour ordering -- 3.4 Single-level system -- References -- 4 Non-equilibrium formalism -- 4.1 Occupation number approach -- 4.2 Two-level system: Pauli spin-blockade -- 4.3 Green function approach -- 4.4 Non-equilibrium Green functions -- 4.5 Single-level quantum dot -- References -- 5 Diagram technique -- 5.1 Decoupling procedure -- 5.2 Expansion using functional derivatives -- 5.3 Single-level quantum dot -- 5.4 Current-voltage asymmetry -- References -- 6 Collection of physical examples -- 6.1 Spin-filtering -- 6.2 Current-voltage asymmetry in double quantum dots -- 6.3 Detection of exchange interaction through Fano-like interference effects -- 6.4 Non-equilibrium triplet blockade in T-shaped double quantum dot -- 6.5 Formation of pure triplet in double quantum dot -- References -- 7 Spin system -- 7.1 Equation for local spin > -- 7.2 Dynamics of local spin: semi-classical approach -- 7.3 Signatures of the local spin in the transport -- References.
Keywords: Physics; Mathematical physics; Optical materials; Nanotechnology; Physics; Mathematical Methods in Physics; Nanotechnology; Solid State Physics; Optical and Electronic Materials; Condensed Matter Physics